1996
DOI: 10.1046/j.1365-2958.1996.412927.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemotactic motility is required for invasion of the host by the fish pathogen Vibrio anguillarum

Abstract: The role of the flagellum and motility in the virulence of the marine fish pathogen Vibrio anguillarum was examined. Non-motile mutants were generated by transposon mutagenesis. Infectivity studies revealed that disruption of the flagellum and subsequent loss of motility correlated with an approximate 500-fold decrease in virulence when fish were inoculated by immersion in bacteria-containing water. However, the flagellar filament and motility were not required for pathogenicity following intraperitoneal injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
137
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(140 citation statements)
references
References 55 publications
3
137
0
Order By: Relevance
“…Consistent with the abnormal function of flagella caused by improper chemotaxis and the reduced virulence in S. typhimurium, Vibrio anguillarum, and Campylobacter jejuni (51)(52)(53), the ppk mutant of P. aeruginosa has been found to be avirulent in a burned-mouse pathogenesis model (A. N. Hamood, personal communication), even though the mutant possesses normal flagella and pili.…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with the abnormal function of flagella caused by improper chemotaxis and the reduced virulence in S. typhimurium, Vibrio anguillarum, and Campylobacter jejuni (51)(52)(53), the ppk mutant of P. aeruginosa has been found to be avirulent in a burned-mouse pathogenesis model (A. N. Hamood, personal communication), even though the mutant possesses normal flagella and pili.…”
Section: Discussionmentioning
confidence: 84%
“…The marine environment is a heterogeneous landscape at the microscale and a bacterium's ability to accurately navigate gradients of nutrients and infochemicals may provide it with a competitive advantage (Taylor and Stocker 2012). Chemotaxis is found governing bacteria − phytoplankton interactions (Bell and Mitchell 1972;Blackburn et al, 1998;Stocker and Seymour 2012), facilitating symbioses such as that between Vibrio fischeri and squid (Mandel et al, 2012), implicated in the onset of disease (Otoole et al, 1996;Banin et al, 2001;Rosenberg and Falkovitz 2004;Larsen et al, 2004;Meron et al, 2009) and common throughout coral reefs (Tout et al, 2015b). Within this framework, reef-building corals are becoming a focal system for studying the role of motility in bacteria-host interactions in the ocean.…”
Section: Discussionmentioning
confidence: 99%
“…However, rpoN is often found to control multiple functions, including flagellar synthesis and nitrogen utilization (41,50,60). Moreover, P. syringae pathovars produce a number of toxins, including syringomycins, tabtoxin, phaseolotoxin, tagetitoxin, and coronatine (6), and we have found that rpoN is required for the expression of coronatine (32).…”
mentioning
confidence: 97%